Karakteristik termogravimetri dan kinetika dekomposisi EPDM dengan bahan pengisi carbon black - Mayasari, Hesty Eka; Yuniari, Arum (Majalah Kulit, Karet, dan Plastik, 2016)
The thermal characteristics of a material are important to learn in order to know the thermal stability of the materials. Ethylene propylene diene monomer (EPDM) is a synthetic rubber that is widely used in industry due to its resistance to aging, ozone, and chemicals. The kinetic parameters and thermal decomposition of vulcanized EPDM were studied using thermogravimetric method with various vulcanization systems (efficient, semi-efficient, and conventional vulcanization system) and various carbon black (CB) as filler (50, 60, and 70 phr). Decomposition consist of two stages; the oxidation of EPDM and volatile matter loss then decomposition of EPDM. Kinetic parameters of the thermal decomposition were approximated by the Coats Redfern equation. Activation energy and decomposed mass increases with decreasing content of CB. Vulcanized EPDM with CB as filler has fairly good resistance against thermal decomposition. The decomposition process can be viewed in detail in this paper.Keywords: EPDM, thermal decomposition, kinetic, thermogravimetric, carbon black.Â